PSIKOLOGI LINGKUNGAN RELIGIUS - Muhammad Hafid; Khairil Anwar; Vivik Shofiah (STKIP Subang, 2026)
The purpose of this article is to examine the concept, role, and implications of religious environmental psychology in shaping student character. Using a descriptive qualitative approach with library research methods, the study explores how religious learning environments encompassing physical, social, and academic factors contribute to student religiosity and mental well-being. The results indicate that a positive school climate, habituation of worship, and the role of teachers as models are fundamental in internalizing Islamic values. Ultimately, a supportive religious environment fosters not only academic achievement but also moral integrity and psychological resilience in students.